City of Strangers Gulf Migration and the Indian Community in Bahrain - Gardner, Andrew M. (Cornell University Press, 2010)
Exploring the everyday experiences of workers from India who have migrated to Bahrain, this study contributes significantly to our understanding of politics and society among the Persian Gulf states and of the migrant labor phenomenon that is an increasingly important aspect of globalization."Andrew M. Gardner expertly combines in-depth ethnography with theoretical sophistication in this important look at the complex linkages between labor, migration, globalization, and the structural violence that accompanies the new world economic order. Gardner follows the labyrinthine paths of migrant workers in the Gulf, drawing on powerful qualitative data to complicate existing assumptions about the lives of skilled and unskilled workers in the Middle East's fastest growing region. Beautifully written and compelling, the book sheds light on a population and area of the world that remains understudied despite its rapid emergence onto the global market."-Pardis Mahdavi, Pomona College